Fluktuasi Nitrat dan Fosfat Selama Satu Periode Pasang dan Surut di Selat Lombok - I Gede Ening Sumantra; Yulianto Suteja; I Nyoman Giri Putra (Fakultas Kelautan dan Perikanan Universitas Udayana, 2020)
Nitrate (NO3-) and phosphate (PO43-) are two parameters of water quality that are important for aquatic organism. Circulation of ocean currents can distribute nitrate and phosphate from one place to another. The current pattern in the waters of the Lombok Strait at the time of the tide moves from the north to the south by bringing the mass of water from the Pacific Ocean, while the movement of the current pattern at low tide moves from south to north by bringing the mass of water from the Indian Ocean. Therefore, this study aims to determine the fluctuations of Nitrate (NO3-) and Phosphate (PO43-) in Lombok Strait during one tidal period. This research was conducted on 3 - 5 November 2017 precisely at coordinates 116?1'18